Daya Saing Ekspor Lada Indonesia ke Amerika Serikat - Desi Anggraini; Syapsan Syapsan; Darmayuda Darmayuda (Convergence: The Journal of Economic Development, 2021)
iThis study aims to determine the competitiveness of Indonesian pepper to the United States, namely to analyze the level of competitiveness, competitiveness position, market concentration of Indonesian pepper exports to the United States. The research used is descriptive quantitative. The research data is the export value and total exports of Indonesian pepper to the United States in 2010-2019. The data used was obtained from the official website of the Food and Agriculture Organization, United Nation Commodity Trade Statistics, the Central Bureau of Statistics, the Directorate General of Plantations and the Ministry of Trade. The results indicate that the RCA for the competitiveness of pepper exports in 2010-2019 has an average value of 30.54 per year, means that Indonesia has a comparative competitiveness of >1. For competitive competitiveness or ECI has experienced a decline in competitive competitiveness because it has an average of 0.94 per year <1. In terms of competitiveness, Indonesia is an exporter country because the ISP value shows an average value of 0.99 per year in the maturation stage. Indonesia has a low dependence on its own trading partner countries, this is indicated by Indonesia's low IKP value of 0.018 with a value of trade intensity (0-1).Keywords :  Indonesian Pepper Exports 1, Revealed Comparative Advantage (RCA)2, Export Competitiveness Index (ECI)3, Trade Specialization Index (ISP) 4, Market Concentration Index (IKP) 5